Susanne Gether collection of negatives, 1890-1911. - Gether, Susanne, 1857-1942 (1890)
Collection of 29 photographs of Susanne Gether, friends, and her and her students' woodcarvings in her workshop in Dunedin, New Zealand, and Sydney, New South Wales, from 1890 to 1911.--Information from acquisitions documentation.
Title from acquisitions documentation.
Also available online
Donated by Elsebeth Hansen, Denmark, 2017.
Keywords: Gether, Susanne, -- 1857-1942 -- Travel -- Photographs; Gether, Susanne, -- 1857-1942 -- Portraits; Danes -- New Zealand -- Photographs; Danes -- Australia -- Photographs; Arts and crafts movement -- Photographs; Wood-carvers -- Denmark -- Photographs; Wood-carvers -- New Zealand -- Photographs; Wood-carvers -- New South Wales -- Sydney -- Photographs; Wood-carving -- Photographs; Wood sculpture -- Photographs; Furniture -- Photographs; New Zealand -- Photographs; New South Wales -- Photographs